Report of the inquiry into the death of Charlie Kulla Kulla - Australia. Royal Commission into Aboriginal Deaths in Custody; Wyvill, L. F. (Canberra : Australian Govt. Pub. Service, 1991)
Death at Coen Watchhouse; report includes personal history , life at Port Stewart, police procedures and care of sick prisoners, treatment at Coen hospital.
Cat. no. 9103946.
At head of title: Royal Commission into Aboriginal Deaths in Custody.
Also available online
Keywords: Kulla Kulla, Charlie, -- 1944-1984.; Police -- Complaints against -- Australia; Prisons and race relations -- Australia; Prisoners, Aboriginal Australian -- Mortality; Law enforcement - Custody - Deaths in custody - Royal Commission; Health services; Law enforcement - Police conduct and attitudes; Coen (Qld NE Cape York SD54-08); Yintjingga / Port Stewart (Qld SE Cape York SD54-12)